System of teenager summer work and rest organization - Kašys, J. (Psichologija, 1968)
Properly organized from pedagogical point of view summer work of teenagers in collective farms (Soviet collective farms), as well as their recreation engrains in teenagers love to agriculture works, fosters their collective, humanist and other feelings. Summer work for children of eight-year rural district schools is an effective means of moral education in such cases when intellectual needs and interests of students are satisfied. Independence, desire to resemble adults, manifestation of feelings of personal worthiness are features characteristic of teenagers. The system of teenager summer work and rest organization for senior students of rural eight-year schools in Soviet collective farms meets such needs of teenagers and boosts their active social inclusion. It also cultivates other competences in teenagers, such as knowledge, material interest, etc.The system of teenager summer activities, consolidating production activities and cultured rest, embraces not only the educational forms of pedagogical management and development of independence in teenagers, but also active participation of the farm communities, especially the management (agriculture specialists, taskmasters, farm managers, etc.) in moral education of children during summer holidays.
Keywords: summer work; summer rest; adolescence